Evaluation of the Arkansas Tobacco Settlement Program Progress Through 2011 - Engberg, John (RAND Corporation, 2012)
In 2001, Arkansas ranked 45th of 50 states on a composite score of all health outcomes. Arkansas is now a regional leader in tobacco control. This final biennial report documents the Arkansas Tobacco Settlement Commission's continued activity and progress, and gauges the effectiveness of the state's seven health-related programs in the past decade. Included is an evaluation of the changes in health outcomes attributed to these programs.